2008
DOI: 10.1158/1055-9965.epi-07-2507
|View full text |Cite
|
Sign up to set email alerts
|

DNA Repair Gene XPD Polymorphisms and Cancer Risk: A Meta-analysis Based on 56 Case-Control Studies

Abstract: Genetic variations in the XPD gene may increase cancer susceptibility by affecting the capacity for DNA repair. Several studies have investigated this possibility; however, the conclusions remain controversial. Therefore, we did a systematic review and executed a meta-analysis to explore the association.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
49
0
1

Year Published

2008
2008
2019
2019

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 72 publications
(54 citation statements)
references
References 64 publications
(17 reference statements)
4
49
0
1
Order By: Relevance
“…Given the lack of direct functional measures of DNA repair capacity associated with the different polymorphisms, it is difficult to integrate the sometime divergent results of the existing studies on XPD and XRCC1. The meta-analyses for XPD and XRCC1 polymorphisms suggested that XPD 751 and XRCC1 399 polymorphisms might not be associated with bladder cancer susceptibility, except that XRCC1 399 Gln/Gln genotype decreased susceptibility of bladder cancer under recessive model and homozygote contract among ever-smokers (30,36,37). The results from our present study suggest that individuals who have the XPD 751 Gln allele may be at an increased risk for bladder cancer, consistent the results of a previous report (28).…”
Section: ------------------------------------------------------------supporting
confidence: 88%
See 1 more Smart Citation
“…Given the lack of direct functional measures of DNA repair capacity associated with the different polymorphisms, it is difficult to integrate the sometime divergent results of the existing studies on XPD and XRCC1. The meta-analyses for XPD and XRCC1 polymorphisms suggested that XPD 751 and XRCC1 399 polymorphisms might not be associated with bladder cancer susceptibility, except that XRCC1 399 Gln/Gln genotype decreased susceptibility of bladder cancer under recessive model and homozygote contract among ever-smokers (30,36,37). The results from our present study suggest that individuals who have the XPD 751 Gln allele may be at an increased risk for bladder cancer, consistent the results of a previous report (28).…”
Section: ------------------------------------------------------------supporting
confidence: 88%
“…The XRCC1 Gln399 polymorphism resulting in single base substitution may affect binding with PARP, leading to a deficiency of DNA repair (27). Epidemiological studies have indicated that these polymorphisms might modify the risk of bladder cancer (4,(28)(29)(30)(31)(32)(33)(34)(35)(36)(37).…”
Section: Introductionmentioning
confidence: 99%
“…13,14 Inherited variations in DNA-repair efficiency have been implicated in the predisposition to de novo 15 and therapy-related AML 16,17 and increased susceptibility to a variety of nonhematologic cancers. 18,19 Therefore, it is reasonable to hypothesize that common polymorphisms in genes encoding for proteins of the NER and BER pathways could influence on the likelihood of developing cancer in patients with ET and PV. To test this hypothesis, in the present study, we investigated the association between 5 single nucleotide polymorphisms (SNPs) of 4 critical genes involved in NER and BER mechanisms and the risk of either leukemic transformation or development of new nonmyeloid malignancies in patients with ET and PV.…”
Section: Introductionmentioning
confidence: 99%
“…Several functional genetic variants, particularly nonsynonymous polymorphisms, have been identified in the XPD, XPG, APE1, XRCC1 and ADPRT genes, and have shown a relationship with DRC variation and susceptibility to multiple cancers (14)(15)(16)(17)(18)(19)(20)(21)(22)(23)(24)(25)(26). Additionally, several reviews were also published to summarize the associations between functional variants of DNA repair genes and cancer risk, including HNC, and have provided meaningful results (17,20,26 …”
Section: Introductionmentioning
confidence: 99%